Gene Expression of Androgen Metabolising Enzymes in Benign and Malignant Prostatic Tissues - Khvostova, E. P.; Otpuschennikov, A. A.; Pustylnyak, V. O.; Gulyaeva, L. F. (Hormone and Metabolic Research, 2015)
Benign prostatic hyperplasia (BPH) as well as prostate cancer (CaP) are prevalent in the aging male population, and both the diseases display androgen-dependence when the circulating testosterone from the gonads decreases. This suggests that the local or intracrine production of androgens may drive these diseases. Both diseases are dependent on the conversion of androgen by the epithelial compartment to the ligand with higher affinity and can be treated by blocking synthesis of this androgen metabolite. For this approach to be effective, a detailed knowledge of androgen biosynthesis in both disease states is required. The aim of the present study was to investigate the gene expression levels of androgen metabolising enzymes in BPH compared to normal adjacent prostate tissues and CaP. Expression of the genes HSD3B1, HSD17B3, and SRD5A2 was significantly increased in BPH tissues compared to normal adjacent prostate tissues. In contrast to BPH, CaP demonstrated significant decrease in the expression of HSD17B3, AKR1C2, and SRD5A2 compared to normal adjacent prostate tissues. HSD17B2 expression was significantly decreased in all samples. Moreover, HSD3B1 and SRD5A2 mRNA levels were upregulated in BPH compared with CaP. These results suggest that a change in androgen metabolism may be an important step in the pathogenesis of BPH, leading to increased cell proliferation due to in situ androgen synthesis. These features can be used to develop differential treatment strategies for BPH. HSD3B1 and SRD5A2 could be used as therapeutic target for BPH.
Keywords: benign prostatic hyperplasia; prostate cancer; androgen biosynthesis